High Prevalence of Asthenopia among a Population of University Students - Hashemi, Hassan; Saatchi, Mohammad; Yekta, Abbasali; Ali, Babak; Ostadimoghaddam, Hadi; Nabovati, Payam; Aghamirsalim, Mohamadreza; Khabazkhoob, Mehdi (Journal of ophthalmic & vision research, 2019)
Purpose: To determine the prevalence of asthenopia and its associated factors in a sample of university students in Iran. Methods: In this cross-sectional study, participants were selected using multistage cluster sampling. Presence of at least one of the 10 symptoms—foreign body sensation, diplopia, blurred vision, eye swelling, dry eye, eye pain, difficulty in sustaining visual operations, decreased visual acuity, tearing, and photophobia—was considered as asthenopia. Ocular examinations, including uncorrected/corrected visual acuity measurement, objective/subjective refraction, cover test, amplitude of accommodation (AA), and near point of convergence (NPC) were performed. Results: Of the 1,462 students (mean age: 22.8 ± 3.1 years), 73% were women. The age- and gender standardized prevalence was 70.9% (95% confidence interval [CI]: 68.3–73.5), 39.8% (95% CI: 36.4–43.1), and 19.7% (95% CI: 16.0–23.3) based on the presence of at least one, two, and three symptoms, respectively. The prevalence was significantly higher in females (P = 0.048), hyperopic students (P < 0.001), and astigmatic participants (P < 0.001). The mean AA and NPC were 9.7 ± 2.6 D and 10.2 ± 4.2 D (P = 0.008) and 7.0 ± 2.1 cm and 7.7 ± 3.9 cm (P < 0.001) in participants with and without asthenopia, respectively. Multiple regression model revealed age (28–29 years), astigmatism, and NPC as independent associated factors (odds ratios: 3.51, 1.61, and 0.91, respectively). Conclusion: This study shows relatively high prevalence of asthenopia in university students. Demographic factors and visual system disorders are important risk factors and timely correction of conditions may lead to decreased asthenopia.